Association between muscular strength and inflammatory markers among elderly persons with cardiac disease: results from the KORA-Age study - Volaklis, K. A.; Halle, M.; Koenig, W.; Oberhoffer, R.; Grill, Eva; Peters, Annette; Strasser, Barbara; Heier, Margit; Emeny, R.; Schulz, Holger; Ladwig, K. H.; Meisinger, Christine; et al. (Clinical Research in Cardiology, 2015)
Little is known about the association between muscle strength and inflammation in diseased individuals and particularly in cardiac patients. Thus, our purpose was to examine the association of muscular strength with the inflammatory status in older adults with and without cardiac disease. The cross-sectional analysis was based on 1079 adults aged 65–94 years, who participated in the KORA-Age study. Participants underwent an interview and extensive physical examinations including anthropometric measurements, registration of diseases and drug intake, determination of health-related behaviors, collection of blood samples for measurements of interleukin-6 and hs-CRP and muscle strength measurement using hand-grip dynamometry. Cardiac patients (n = 323) had higher levels of IL-6 and poorer muscle strength compared with older adults without cardiac disease. Among persons with cardiac diseases, muscle strength in the lower tertile compared to the upper tertile was significantly associated with increased odds of having elevated IL-6 levels (OR 3.53, 95 % CI 1.18–10.50, p = 0.024) after controlling for age, gender, body fat, alcohol intake, smoking status, diseases, medications and physical activity, whereas the association between muscle strength and hs-CRP remained borderline significant (OR 2.80, 95 % CI 0.85–9.24, p = 0.092). The same trends, with slightly lower odds ratios, were also observed in older adults without cardiac disease. Lower levels of muscular strength are associated with higher concentrations of IL-6 and hs-CRP in elderly individuals with and without cardiac disease suggesting a significant contribution of the muscular system in reducing low-grade inflammation that accompanies cardiac disease and aging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aging; Cardiac disease; Inflammation; Muscle strength